How do you solve $$ \begin{cases}u_t-\frac{x}{t^2+1}u_x=0, & x,t\in\mathbb{R}\\u(0,x)=u_0(x)\in C^1(\mathbb{R})\end{cases} $$ by the method of characteristics?

My approach is to consider the parametrisation $t=t(\tau,\xi), x=x(\tau,\xi), u=u(\tau,\xi)$. Then the ODE to solve are $$ \begin{align*} &\frac{dt}{d\tau}=1\\ &\frac{dx}{d\tau}=-\frac{x}{t^2+1}\\ &\frac{du}{d\tau}=0 \end{align*} $$ with initial conditions $$ \begin{align*} &t(0,\xi)=0\\ &x(0,\xi)=\xi\\ &u(0,\xi)=u_0(\xi). \end{align*} $$ Solving this, what I get is $$ t=\tau,\quad u=u_0(\xi),\quad x=-\frac{x}{t^2+1}t+\xi. $$

(Does this make sense? I have the feeling that it should be $x(t,\xi)=-\frac{\xi}{t^2+1}t+\xi$ instead.)

I have two questions:

(A) Isn't the right-hand side of $$ \frac{dx}{d\tau}=-\frac{x}{t^2+1} $$ globally Lipschitz continuous with respect to the second argument $x$, since $$ \left\lvert\frac{-x_1+x_2}{t^2+1}\right\rvert\leqslant \lvert x_2-x_1\rvert? $$ Doesn't this imply that this ODE has a unique global solution defined for all $(x,t)\in\mathbb{R}^2$ which then implies that the given PDE above has a unique global solution?

(2) How can I get an explicit expression of $u(x,t)$ depending on $u_0$?


1 Answer 1


$$u_t-\frac{x}{t^2+1}u_x=0$$ The Charpit-Lagrange system of ODEs is : $$\frac{dt}{1}=\frac{dx}{-\frac{x}{t^2+1}}=\frac{du}{0}$$ A first characteristic equation comes from $\frac{du}{0} \quad\implies\quad du=0$ $$u=c_1$$ A second characteristic equation comes from $\frac{dt}{1}=\frac{dx}{-\frac{x}{t^2+1}}$ which is separable. Solving it leads to : $$xe^{\tan^{-1}(t)}=c_2$$ The general solution expressed on the form of implicit equation $c_1=F(c_2)$ is : $$u(x,t)=F(xe^{\tan^{-1}(t)})$$ $F$ is an arbitrary function, to be determined according to the condition : $$u(x,0)=u_0(x)=F(xe^{\tan^{-1}(0)})=F(x)$$ Now the function $F(X)$ is determined whatever the variable $X$ is : $$F(X)=u_0(X)$$ We put this function into the above general solution where $X=xe^{\tan^{-1}(t)}$.

The particular solution satisfying the specified condition is : $$u(x,t)=u_0(xe^{\tan^{-1}(t)})$$


Change of variables : $$\theta=\tan^{-1}(t)$$ $$\xi=\ln|x|$$ The PDE is transformed into : $$u_\theta-u_\xi=0$$ I suppose that you know how to solve it with the method of characteristic or other method. The general solution is $$u(\xi,\theta)=f(\xi+\theta)$$ $f(\chi)$ is an arbitrary function, with $\chi=\xi+\theta$ .

Let $f(\chi)=F(e^\chi)$ where $F$ is an arbitrary function since $f$ is arbitrary. $$u(\xi,\theta)=F(e^{\xi+\theta})$$ $e^{\xi+\theta}=xe^{\tan^{-1}(t)}$ $$u(x,t)=F(xe^{\tan^{-1}(t)})$$

  • $\begingroup$ I get that $u=xe^{\tan^{-1}(t)}e^{-\tan^{-1}(0)}$. I do not see how I now get $u_0$ into this. $\endgroup$
    – Salamo
    Nov 16, 2019 at 13:51
  • $\begingroup$ This is shown in the first part of my answer. The particular solution satisfying the specified condition is : $$u(x,t)=u_0(xe^{\tan^{-1}(t)})$$ $\endgroup$
    – JJacquelin
    Nov 19, 2019 at 18:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.